2006
DOI: 10.1007/s10653-006-9048-y
|View full text |Cite
|
Sign up to set email alerts
|

Biomineralogy of human urinary calculi (kidney stones) from some geographic regions of Sri Lanka

Abstract: Kidney stones (urinary calculi) have become a global scourge since it has been recognized as one of the most painful medical problems. Primary causative factors for the formation of these stones are not clearly understood, though they are suspected to have a direct relationship to the composition of urine, which is mainly governed by diet and drinking water. Sixty nine urinary calculi samples which were collected from stone removal surgeries were analyzed chemically for their Na, K, Ca, Mg, Cu, Zn, Pb, Fe and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 16 publications
1
25
0
Order By: Relevance
“…The quantitative phase analysis of KS5, KS6 (Fig. 4) and KS7 showed varying amounts (1.9-17.3 wt%) of the APP phase along with the COM phase (82.7-98.1 wt%), and that of KS8 ( urinary calculi samples KS1-KS8 are in good agreement with the composition of kidney stones from patients in other parts of the Indian subcontinent (Ansari et al, 2005;Satish et al, 2008;Chandrajith et al, 2006).…”
Section: X-ray Studiessupporting
confidence: 60%
See 1 more Smart Citation
“…The quantitative phase analysis of KS5, KS6 (Fig. 4) and KS7 showed varying amounts (1.9-17.3 wt%) of the APP phase along with the COM phase (82.7-98.1 wt%), and that of KS8 ( urinary calculi samples KS1-KS8 are in good agreement with the composition of kidney stones from patients in other parts of the Indian subcontinent (Ansari et al, 2005;Satish et al, 2008;Chandrajith et al, 2006).…”
Section: X-ray Studiessupporting
confidence: 60%
“…(APP), Ca 10 (PO 4 ) 6 (OH) 2 ] and uric acid (UA, C 5 H 4 N 4 O 3 ) are commonly found in human urinary stones (Joseph et al, 2005), the whewellite (COM) phase is the most common (Daudon et al, 2009). Several studies have been reported which survey the mineral phases of urinary stones from different parts of Europe (Leusmann, 1991), the USA (Kim, 1982), South Africa (Laing & Kerr, 1991), Canada (Levinson et al, 1985), Brazil (Orlando et al, 2008), Sri Lanka (Chandrajith et al, 2006) and India (Ansari et al, 2005). Analytical methods such as chemical analysis, polarizing optical microscopy, Fourier transform IR (FT-IR) spectroscopy and X-ray powder diffraction are generally used for qualitative and quantitative classification of urinary calculi (Rodgers et al, 1982;Spector et al, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…There is a high correlation between the formation of kidney stones, and non-vegetarian food habits, a diet rich in animal protein may increase the risk of kidney stones, and however, vegetarian diet has a lower risk for the formation of kidney stones (Sandilya and Sandilya 2019). Consuming the high amount of animal meat will lead to the acidification of urine which may lead to the formation of calcium oxalate stone in the urinary tract (Chandrajith et al 2006), it could also alter the renal function or increasing the intestinal absorption of calcium which will lead to the formation of calcium-based kidney stone (Licata et al 1979). And also, the consumption of meat with the combination of protein-rich food had a significant association with the prevalence of urinary tract stones (Basiri et al 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Although rare, classifications based on morphological appearance of renal stones may give more information on the history 28 A study based on artificial urine has revealed that the possibility for the formation of calcium oxalate is higher than that of calcium phosphate. Further, calcium oxalate is the commonest and an important constituent for renal calculi 33 34 . These studies described the variation of chemical composition of renal stones with respect to the geographical location of the country and the incidence rate of stag horn calculi.…”
Section: Anatomical Location Of Human Renal Stones Mechanism Of Nuclmentioning
confidence: 99%